The Drosophila SOX-domain protein Dichaete is required for the development of the central nervous system midline. - Sanchez Soriano, N.; Russell, S. (Development, 1998)
SOX-domain proteins are a class of developmentally important transcriptional regulators related to the mammalian testis determining factor SRY. In common with other SOX-domain genes, the Drosophila Dichaete gene has a dynamic expression profile in the developing central nervous system, including cells of the ventral midline. We find defects in the differentiation of midline glia and concomitant axonal defects in Dichaete mutants that are rescued by driving Dichaete expression in the midline. Since Dichaete is required for the correct specification or differentiation of midline glia, we have used the ventral midline as a model system to study SOX gene function in vivo and demonstrate a genetic interaction between Dichaete and the POU domain gene ventral veinless. In mammals, a protein related to Dichaete, SOX2, also interacts with POU transcription factors. The midline phenotypes of Dichaete mutations are rescued by expression of mouse SOX2. Our data suggest that SOX gene structure, function and interactions have been conserved during evolution.